A novel 10-membered macrocyclic lactone from the mangrove-derived endophytic fungus Annulohypoxylon sp. Issue 7 (14th February 2018) - Liu, Yang; Kurtán, Tibor; Mándi, Attila; Weber, Horst; Wang, Changyun; Hartmann, Rudolf; Lin, Wenhan; Daletos, Georgios; Proksch, Peter
Graphical abstract: Highlights: Annulohypoxylon sp. was obtained from the Mangrove plant Rhizophora racemosa . An unprecedented macrolactone, hypoxylide, was isolated from Annulohypoxylon sp. The absolute configuration of hypoxylide was established by ECD spectroscopy. A plausible biosynthetic pathway of hypoxylide is discussed. Abstract: A novel 10-membered macrolactone, hypoxylide (1 ), was isolated from the endophytic fungus Annulohypoxylon sp. that was obtained from the Mangrove plant Rhizophora racemosa . The structure and absolute configuration of1 were unambiguously elucidated by comprehensive 1D and 2D NMR, as well as by HRESIMS and ECD spectroscopic analyses. Hypoxylide (1 ) features an unprecedented polyketide skeleton comprised of a trihydroxynaphthalene-dione moiety fused to a decalactone ring. A plausible biosynthetic pathway of this novel metabolite is proposed.